2008
DOI: 10.1071/ea07414
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal protein degradability of a range of tropical pastures

Abstract: Abstract. The rumen degradability parameters of the diet selected by two to four oesophageal-fistulated Brahman steers grazing a range of tropical pastures were determined by incubation of extrusa in nylon bags suspended in the rumen of rumen-fistulated (RF) Brahman steers. The effective protein degradability (Edg) was determined by measuring the rate of disappearance of neutral detergent insoluble nitrogen (NDIN) less acid detergent insoluble nitrogen (ADIN) in the incubated extrusa. Six to eight RF steers al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…The CP content found in pastures in the current study was relatively high, reflecting the plant growth stage and the use of N fertilizer. Assuming a ruminal degradability of protein of 800 g/kgCP (Bowen et al, 2008),it would result in rumen degradable protein (RDP)/digestible organic matter (DOM) ratios of 195 and 197 g RDP/kg DOM for both grazing intensities, values that are in excess of the RDP requirements for microbial protein synthesis in the rumen (CSIRO, 2007). The lower ADG observed in the high grazing pressure is primarily a result of the lower FM allowance used for that pasture management, but could also be linked to harvesting constraints and/or lower availability of leaves in the lower strata, as suggested by the differences found in morphological composition between the post-grazing FM in both treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The CP content found in pastures in the current study was relatively high, reflecting the plant growth stage and the use of N fertilizer. Assuming a ruminal degradability of protein of 800 g/kgCP (Bowen et al, 2008),it would result in rumen degradable protein (RDP)/digestible organic matter (DOM) ratios of 195 and 197 g RDP/kg DOM for both grazing intensities, values that are in excess of the RDP requirements for microbial protein synthesis in the rumen (CSIRO, 2007). The lower ADG observed in the high grazing pressure is primarily a result of the lower FM allowance used for that pasture management, but could also be linked to harvesting constraints and/or lower availability of leaves in the lower strata, as suggested by the differences found in morphological composition between the post-grazing FM in both treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Values of effective rumen degradable protein (ERDP) give an estimate of N supply to microbes for grazing ruminants (Bowen et al, 2008). Higher and lower supplies of ERDP were obtained for NF-DH2 (222.8 g kg −1 DM) and NNF-DH2 (114.9 g kg −1 DM), respectively.…”
Section: Crude Protein Degradation Kineticsmentioning
confidence: 99%
“…Although Ogden (5) showed that in C4-grasses the rate of digestion of the NDIP fraction is faster than its own NDF fraction (11.0 vs 7.8 %/h). In Australian tropical grasses measuring NDIP rates of digestion found a range between 4.7 and 7.9 %/h (6) . However, Singh (2) for tropical grasses in India consider the Sniffen digestion rate of fiber-bound protein of less than 1.5 %/h (7) .…”
Section: Recibido 15/05/2017mentioning
confidence: 99%
“…Also, in Brazilian grasses (8) reported digestion rates between 0.08 and 1.3 %/h for the PB3 fraction. At a given passage rate of 2.5 %/h Ogden (5) or a range between 2.0-4.4 %/h Bowen (6) it is critical to know if the NDIP digestion rate exceeds or not the passage rate. Because grasses frequently make up the only source of protein for many ruminants, information on the NDIP fraction of grasses is a prerequisite to modeling the N economy of ruminants.…”
Section: Recibido 15/05/2017mentioning
confidence: 99%
See 1 more Smart Citation